Categorizing urban avoiders, utilizers, and dwellers for identifying bird conservation priorities in a Northern Andean city - Garizábal-Carmona, Jaime A.; Betancur, Jefry S.; Montoya-Arango, Sergio; Franco-Espinosa, Laura; Mancera-Rodríguez, N. Javier (Frontiers in Ecology and Evolution, 2024)
IntroductionCategorizing species according to their frequencies across urbanization levels and identifying some species traits that explain this variation could be a valuable tool for focusing conservation efforts, particularly in biodiversity hotspots with high endemism rates. This study proposes a semi-quantitative and multi-scale protocol to categorize bird species as urban avoiders, utilizers, and dwellers, based on their frequencies at different urbanization levels. Additionally, it evaluates the relationships of these categories with altitudinal ranges, trophic guilds, and foraging strata.MethodsWe performed bird counts in 124 points located within urban areas, and in 15 points located in non-urban areas of a Colombian Northern Andean city (Medellín and surroundings). Each urban point was assigned to urbanization levels based on 200, 500, and 1,000 m buffers categorized as high (67–100% of built cover), moderate (34–66% of built cover), or low (0–33% of built cover).ResultsWe categorized 103 bird species: 49 as urban avoiders, 31 as urban utilizers, and 23 as urban dwellers. The two recorded Colombian endemic species and seven near-endemics were categorized as urban avoiders, with only one near-endemic species categorized as an urban utilizer (the other three were data deficient). Furthermore, most bird species with exclusive Andean distribution were categorized as urban avoiders (78.57%). Urban avoiders had narrower altitudinal ranges (1,969 ± 524 m) than utilizers (2,287 ± 592m) and dwellers (2,569 ± 654m), and they had the largest proportion of frugivorous and frugivorous-insectivorous species, while urban dwellers had a greater proportion of omnivorous species. Overall, bird species with exclusive Andean distribution and narrow altitudinal ranges are the most threatened by urban sprawl, irrespective of their trophic guild or foraging strata.DiscussionThis study emphasizes the importance of protecting native forest remnants in urban surroundings for conserving native Andean bird species, as urban green spaces in high-density cities may not sufficiently support their long-term survival and reproduction. Also, it highlights the need to identify conservation priorities based on local biodiversity patterns, taking into account that species-specific urban tolerance depends on particular landscape dynamics and species regional pools.